2013
DOI: 10.1371/journal.pone.0080619
|View full text |Cite
|
Sign up to set email alerts
|

Calf-Level Factors Associated with Bovine Neonatal Pancytopenia – A Multi-Country Case-Control Study

Abstract: Bovine neonatal pancytopenia (BNP), a high fatality condition causing haemorrhages in calves aged less than 4 weeks, was first reported in 2007 in Germany and subsequently observed at low incidence in other European countries and New Zealand. A multi-country matched case-control study was conducted in 2011 to identify calf-level risk factors for BNP. 405 BNP cases were recruited from 330 farms in Belgium, France, Germany and the Netherlands by laboratory confirmation of farmer-reported cases. Up to four calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…The following Pfizer personnel were observers during the study: Jeremy Salt, Michael Pearce, Tony Simon and Marie‐Odile Hendrickx. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript, except attendance at project coordination meetings as observers, and commenting on the draft manuscript.119 …”
Section: Transparency 22(a) Give the Source Of Funding And The Rolmentioning
confidence: 99%
“…The following Pfizer personnel were observers during the study: Jeremy Salt, Michael Pearce, Tony Simon and Marie‐Odile Hendrickx. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript, except attendance at project coordination meetings as observers, and commenting on the draft manuscript.119 …”
Section: Transparency 22(a) Give the Source Of Funding And The Rolmentioning
confidence: 99%
“…Thus these factors will contribute to variability in the likelihood of a calf developing BNP and the extent of alloantibody-induced pathology ( Figure 2) [26].…”
Section: Bnp Is An Alloimmune Disease Induced By Antibodies Absorbed mentioning
confidence: 99%
“…Epidemiological studies demonstrated a significant association between BNP and the administration of a specific vaccine (Pregsure© BVD, Pfizer Animal Health) to the mothers of affected calves [26][27][28] and showed that the incidence of BNP was higher in herds that received multiple doses of the vaccine [10]. It was also notable that those European countries that remained free from BNP prohibited the use of this and all other BVD vaccines, due to alternative disease control policies.…”
Section: Vaccination Induces Bnp-associated Alloantibodiesmentioning
confidence: 99%
See 2 more Smart Citations